27x-3=

Simple and best practice solution for 27x-3= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 27x-3= equation:


Simplifying
27x + -3 = 0

Reorder the terms:
-3 + 27x = 0

Solving
-3 + 27x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + 27x = 0 + 3

Combine like terms: -3 + 3 = 0
0 + 27x = 0 + 3
27x = 0 + 3

Combine like terms: 0 + 3 = 3
27x = 3

Divide each side by '27'.
x = 0.1111111111

Simplifying
x = 0.1111111111

See similar equations:

| 2x+x+2=99-x+1 | | x=y^3-3y^2+3y | | b+4-1=5 | | -4x(x-6)(x-4)=0 | | 80-x-52=5 | | e=1/9*3.14*x*x*2p | | 5(p-7)=5 | | e=1/9*3.14x2p | | 8+4m=14+2m | | 8x-12y=13 | | 5h+6(1.2-h)=7 | | 6h+5(1.2-h)=7 | | 8u=-u^2+1 | | 4.5/0.5 | | 80t=7 | | t(6+8.4)=7 | | 2/0.02 | | 0.02/2 | | 5/0.18 | | 5m*1.2=90 | | -4x(6-x)(4-x)=0 | | 13x+5=11x-2 | | 5t+(6t-1.2)=90 | | (8n-1)(3n-5)=(4n+3)(6n+5) | | 5t+6(1.2-t)=90 | | 6m+4=4(-m-2) | | 5t+t(1.2-t)=90 | | 15=-5/9v | | t*5=(1.2-t)6 | | 6a+3(a-20)=399 | | Y=-5x^2+7x+4 | | Y=-2x^2+7x+4 |

Equations solver categories